Pemberdayaan Masyarakat Lokal Dalam Pengembangan Potensi Ulos Ragi Hotang di Desa Meat Kecamatan Tampahan Kabupaten Toba - Putri Sapta Maria Silitonga; Wolter P Silalahi; Rusmauli Simbolon; Mery Silalahi; Eduward Hottua Hutabarat (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study examines community empowerment in the development of Ulos Ragi Hotang in Desa Meat, Kecamatan Tampahan, Kabupaten Toba. Ulos Ragi Hotang is a cultural heritage of Batak Toba, rich in philosophical and historical meaning, with great potential as a creative economy product. The focus of this research is on the forms and strategies of community empowerment to preserve cultural heritage, increase economic added value, and support Desa Meat as a cultural tourism destination. The research uses a qualitative descriptive approach with data collection through observation, in-depth interviews with local weavers, traditional leaders, Pokdarwis managers, and the Tourism Department, as well as field documentation. The results show that empowerment is carried out through the improvement of weaving skills, community-based weaving groups, and training in production and marketing. Empowerment strategies include traditional marketing, digital promotion, strengthening tourism village institutions, product branding development, and involving the younger generation. Supporting factors include local cultural wealth and government support, while challenges include low digital literacy and limited market access. This study concludes that local community empowerment plays a significant role in the preservation of Ulos Ragi Hotang and creates sustainable creative economic opportunities, while also strengthening the cultural identity of Batak Toba.